Les Tables de la Loi, même brisées, ont leur place dans l’Arche sainte: vieillesse et vieillissement dans la tradition juive (Halakhah et Hagaddah) - Licari, François-Xavier (De senectute, 2023)
This article explores some representations of old age in the Bible and in rabbinic literature. This exploration reveals the tensions between idealized images of old age on the one hand, and the social less shining realities of aging on the other hand. This literature narrates a lot of stories illustrating the fears associated with aging: from the loss of physical capability and beauty to the loss of memory and mental health, and from marginalization in the community to being experienced as a burden by one’s children. Showing a deep compassionate ethos, Hagaddah and Halakhah promote the respect and reverence of elder people and parents, and also harmonious intergenerational relationship.